A new freshwater prawn species of the genus Macrobrachium Bate (Decapoda, Caridea, Palaemonidae) from South Vietnam - Binh, Le Thi (Academia Journal of Biology, 2006)
During the study of freshwater prawn in the Dongnai river, we have found a new species to science of the genus Macrobrachium Bate. This species was collected from the TaLai village, Tanphu district, Dongnai province, belonging to the Cattien national park. Macrobrachium talaiense Le sp. nov. The body length is about 30-50 mm. The carapace is smooth. The rostrum is short, quite straight, reaching slightly beyond the antennular peduncle. The upper margin bears 8 to 10 teeth (generally 9), two or three of which are situated on the carapace; the lower margin bears 3 to 4 teeth (generally 3) near the apex. The second pereiopods are almost equal and slender, its segments are cylindrical, smooth. The merus is about as long as or slightly longer than carpus. The carpus is longer than the palm. The fingers of the second pereiopods are ¾ as long as the palm. The cutting edge of the dactylus is smooth and bears two small denticles on the base of its.